Evaluation of Land Suitability for Pepper Plants (Piper Nigrum Linn) in Kindang District, Bulukumba Regency - Zhiddiq, Sulaiman; Badwi, Nasiah; Haeril, A. Khaerul Anam (UNIVERSITAS NEGERI MAKASSAR, 2021)
This study aims to determine the characteristics of the land and determine land suitability for pepper (Piper Nigrum Linn) in Kindang District, Kab. Bulukumba. The type of this research is descriptive quantitative research by using survey method of soil observation. In this study, using purposive sampling data collection techniques on eleven land units by taking samples of undisturbed soil. The results of this study indicate the characteristics of the land in the research location, namely wet climate; medium temperature ; availability of water and high rainfall; good drainage; the dominant texture class is smooth and slightly fine; medium coarse fraction; good effective depth; high clay CEC value; medium base saturation; non sodic alkalinity; erosion hazard levels that range from very low to very severe; no flood hazard; and medium land preparation. The actual land suitability class) consists of: class S2 (fairly suitable) covering an area of 36.5 km2, class S3 (marginally appropriate) covering an area of 52.6 km2 class N (not suitable) covering an area of 54,3 km2.